IMPROVING THE METHODOLOGY OF TEACHING TERMINOLOGICAL LEXICON TO STUDENTS IN THE FIELD OF ELECTRICAL ENERGY (Лучшие интеллектуальные исследования, 2025)
Annotation: This article discusses the stages and levels of improving the methodology of teaching terminological lexicon to students specializing in the field of electrical energy. It outlines various strategies to enhance their understanding and usage of technical terms, while also analyzing the effectiveness of various teaching approaches. The study emphasizes the importance of aligning teaching methodologies with students’ learning needs and industry requirements.